How fast is the frequency of precipitation extremes doubling in global land regions? - Guillaume Chagnaud; Juliette Blanchet; Guillaume Evin; Benoit Hingray; Thierry Lebel; Geremy Panthou; Théo Vischel (Environmental Research Communications)
The increasing frequency and intensity of precipitation extremes poses a serious challenge for societies that must adapt to a changing climate. Communicating these changes in terms of their magnitude at a given lead time (e.g., 2100) or at a given level of global warming (e.g., +2 °C) can give the misleading impression that climate change is a distant issue; yet, adaptation measures to cope with future hydro-climatic conditions may be designed and implemented today. Contextualizing the potential future consequences of precipitation intensification in a current temporal frame of reference may help perceive climate change as an ongoing phenomenon, in turn encouraging adaptation planning. Using an ensemble of climate models from Phase 6 of the Coupled Model Intercomparison Project (CMIP6) in a non-stationary extreme value framework, we quantify the time it takes for the frequency of extreme 1-day and 7-day precipitation accumulations –as estimated in the current climate– to double; the frequency double time (FDT) is estimated for a range of event rarities over land regions. Vast parts of the Northern Hemisphere high-latitudes are found to have FDT  <  80 years. Substantial parts of some densely populated mid-latitude regions have FDT in the next 5–6 decades for some rare events. The fastest frequency doubling, in the coming two decades, is found in the highly vulnerable tropical regions of Western and South Eastern Africa, with strong implications for hydrological risk management there. In addition, the rarest events are found to have smaller FDT compared to more ‘common’ extremes; infrastructures designed to withstand the strongest events are thus more exposed to premature obsolescence.